Obremenitveni funkcijski testi hoje pri pljučnem bolniku - Žen Jurančič, Marijana (Rehabilitacija (Ljubljana), 2010)
Six-minute walk test (6-MWT) is most used functional exercise test of walking. It is used as a measure of functional activity. The covered distance is also an indicator of mortality in chronic heart failure, chronic obstructive pulmonary disease (COPD), and primary pulmonary hypertension. Incremental Shuttle Walk Test (ISWT) was developed in the last decade as a modification of 6-MWT for COPD patients. The results of this test, expressed as distance in metres, are significantly correlated with the results of cardiopulmonary exercise testing.
Keywords: cardiovascular disease; diagnostika; funkcijski test; hoja; kardiovaskularne bolezni; krožni test hoje; obremenitveni test; pljučne bolezni; prehojena razdalja; vzdržljivost